2022
DOI: 10.1371/journal.pmed.1003862
|View full text |Cite
|
Sign up to set email alerts
|

GP-delivered medication review of polypharmacy, deprescribing, and patient priorities in older people with multimorbidity in Irish primary care (SPPiRE Study): A cluster randomised controlled trial

Abstract: Background There is a rising prevalence of multimorbidity, particularly in older patients, and a need for evidence-based medicines management interventions for this population. The Supporting Prescribing in Older Adults with Multimorbidity in Irish Primary Care (SPPiRE) trial aimed to investigate the effect of a general practitioner (GP)-delivered, individualised medication review in reducing polypharmacy and potentially inappropriate prescriptions (PIPs) in community-dwelling older patients with multimorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 53 publications
3
46
0
Order By: Relevance
“…We found an overall pooled prevalence of polypharmacy amongst patients with CLD at 31%. Despite the apparent disparity in the underlying liver pathology amongst the included studies, our period prevalence estimate provides the rst attempt at exploring the burden of this growing therapeutic morbidity in these cohorts of patients and falls within the "ballpark" reported in the general population (20)(21)(22)4). Data from pharmaco-epidemiological studies in patients with alternative morbidities such as people living with HIV/AIDS (PLWHA) has shown that amongst the factors that drive adverse consequences of polypharmacy in them includes the inherent propensity of parent ART drugs to bidirectional interactions; as well as the metabolizing pathways of some of the ART drugs which are highly polymorphic and therefore prone to pharmacogenetic interactions (23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%
“…We found an overall pooled prevalence of polypharmacy amongst patients with CLD at 31%. Despite the apparent disparity in the underlying liver pathology amongst the included studies, our period prevalence estimate provides the rst attempt at exploring the burden of this growing therapeutic morbidity in these cohorts of patients and falls within the "ballpark" reported in the general population (20)(21)(22)4). Data from pharmaco-epidemiological studies in patients with alternative morbidities such as people living with HIV/AIDS (PLWHA) has shown that amongst the factors that drive adverse consequences of polypharmacy in them includes the inherent propensity of parent ART drugs to bidirectional interactions; as well as the metabolizing pathways of some of the ART drugs which are highly polymorphic and therefore prone to pharmacogenetic interactions (23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%
“… 45 Supplementing the SENATOR recommendations with the patient’s individual preferences might substantiate the proposed medication changes and improve the outcome of this intervention as shown in the SPPiRE study, which also used the STOPP/START criteria but supplemented them with an assessment of patient priorities and whose recommendations were well received. 46 …”
Section: Discussionmentioning
confidence: 99%
“…45 Supplementing the SENATOR recommendations with the patient's individual preferences might substantiate the proposed medication changes and improve the outcome of this intervention as shown in the SPPiRE study, which also used the STOPP/START criteria but supplemented them with an assessment of patient priorities and whose recommendations were well received. 46 Besides the small sample size other limitations of our pilot study have to be addressed. Individuals who volunteer to participate in a study may be more open-minded and attentive during preference elicitation than other members of the target group.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 5 years, several multicentre randomised controlled trials (RCTs) have attempted to address some of these limitations. The SPPiRE (Supporting Prescribing in Older Adults with Multimorbidity in Irish Primary Care) cluster RCT involving 51 Irish general practices enrolled 404 multimorbid patients aged 65 years or over and receiving 15 or more regular medicines 7 . Intervention practices accessed a website for clinicians to complete an education module and use a template for a once‐off patient medication review lasting 30–40 minutes.…”
Section: Efficacy and Safety Of Deprescribing Interventionsmentioning
confidence: 99%